(untitled) (Research, Society and Development, 2021)
Angle Class III malocclusion results in aesthetic and functional concerns, thus it is essential that this malocclusion is treated as early as possible, so that dentocraniofacial development occurs properly. A 7-year-old male patient with Asperger’s syndrome had a Class III subdivision right malocclusion, anterior and posterior crossbite. To gain the patient’s trust and collaboration, we used the behavioral management technique tell-show-do, in addition to the behavioral analysis method. Orthodontic treatment started using the Hyrax palatal expander, but the patient was not able to adapt to it. Correction of the crossbite was achieved using a removable expander with digital springs, which was better accepted by the patient and provided aesthetic and functional improvement.